Regional differences of physical fitness and overweight and obesity prevalence among college students before and after COVID-19 pandemic since the “double first-class” initiative in China - Jiang, Qing; Huang, Xin; Wang, Zuoliang; Dai, Xinghong; Li, Rongxuan; Cui, Di (Frontiers in Public Health, 2024)
Introduction Physical fitness has been widely recognized as a powerful marker of health in children and adolescents, and it negatively affected by the COVID-19 pandemic. The construction of world-class universities and first-class disciplines, known as the “Double First-Class” Initiative (DFC), is a major commitment made by the Chinese government to adapt to changes in the educational environment, both domestically and internationally, in order to promote the development and practice of international higher education. The aim of the study was to look deep into the regional differences of physical fitness and overweight and obesity prevalence among college students before and after the COVID-19 pandemic since the DFC. Methods The original physical fitness parameters of students from 10 DFC universities and colleges in Central South China were downloaded from the official website of Chinese National Student Physical Fitness Database (CNSPFD) and then divided into 3 groups based on the pandemic periods: pre-pandemic (2019), the first year after pandemic outbreak (2020), and the second year after pandemic outbreak (2021). All the data were stored in Excel 2010, analyzed by SPSS 17.0, and plotted with ArcGIS 10.4. Results The total “fail” percentage (from 9.19% in 2019 to 12.94% in 2021) and the prevalence of overweight and obesity in boys (from 22.53 to 29.25% in 2021) exhibited a continuous increase year by year, and among all the physical fitness indicators the score of strength in boys and endurance quality in all individuals were the lowest in overweight and obesity groups. Students with ‘fail’ rate developed from northern and northeastern province to southern areas from 2019 to 2021. For grade 2019th, overweight and obesity students who also failed the test had covered nationwide and the most affected areas including northeast, east, as well as central north in senior year. The distribution of overall fitness assessments in Hubei province was in accordance with the national data, and the overall scoring growths in both class of 2021st and 2022nd were measured with a negative increase (p < 0.01). Conclusion The government and related functional departments should take into consideration the student regional sources, especially in western and northeast regions of China, and school polices and physical education (PE) teachers should pay more attention to put training efforts on endurance for all adolescents and strength for boys and the group of overweight and obesity who also failed in the standard test, when designing specific interventions to promote physical health and counteract the negative effects of COVID-19 pandemic in college students.